Fifty Years of the Panel Study of Income Dynamics: Past, Present, and Future. Issue 1 (November 2018) - Johnson, David S.; McGonagle, Katherine A.; Freedman, Vicki A.; Sastry, Narayan
The Panel Study of Income Dynamics (PSID) is the world's longest running household panel survey. Since it began in 1968, it has collected data on the same families and their descendants, making it an essential part of America's data infrastructure for empirically based social science research. The PSID arose from the War on Poverty as a tool for evaluating poverty dynamics, and this year (2018) marks 50 years of data collection. Because of its long history and distinctive design of following adult children as they form their own households, the PSID is uniquely positioned to address emerging social and behavioral research questions and related policy issues. This overview presents the design and structural aspects and its evolution over the past 50 years, the successes of the current survey, possible future directions, and the value of using the PSID to understand the challenges facing American families.